How pervasive and mobile computing can help organizations to include people with visual disabilities on their client-approach strategy? - Cunha, Carlos R. (2012)
Organizations have in-built social responsibility to society. The evolution of technology have enable organizations to interact in an innovatively and more close approach to their clients. But this evolution has not included people with special needs like blind people. And, even those organizations that have enable some kind of support-approach to blind people, have typically disjointed, incomplete and typically parallel approaches; compared to their massclient standard approach. This paper discusses the potential of Pervasive and Mobile Computing to support, not just an innovative and unified approach, but also a real possibility of promoting real inclusion of blind people in what concerns to the delivery of information and services organizations offer. This paper also represents a reflection and a mind shaking attempt, while the authors are working in allowing blind people an autonomous buying process, in hypermarkets, supported by the use of wireless networks and modern mobile devices, with multiple technologies support, like Wi-Fi and inertial and magnetic sensors.